Detection of mosaicism for 46,X,i(Y) (q10) in the blood lymphocytes in a phenotypically normal male neonate with prenatally detected 45,X/46, XY at amniocentesis and cytogenetic discrepancy in various tissues - Chih-Ping Chen; Schu-Rern Chern; Shin-Wen Chen; Fang-Tzu Wu; Chen-Chi Lee; Wen-Lin Chen; Yun-Yi Chen; Wayseen Wang (Elsevier, 2022)
Objective: We present detection of mosaicism for 46,X,i(Y) (q10) in the blood lymphocytes in a phenotypically normal male neonate with prenatally detected 45,X/46, XY at amniocentesis and cytogenetic discrepancy in various tissues. Case report: A 35-year-old, gravida 2, para 1, woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 45,X [8]/46,XY [15]. Simultaneous array comparative genomic hybridization (aCGH) on uncultured amniocytes revealed the result of arr (Y) × 0-1 with 25.493-Mb mosaic deletion of chromosome Yp11.31-q11.23. Prenatal ultrasound findings were unremarkable. The fetus had normal male external genitalia on fetal ultrasound. Following genetic counseling, the pregnancy was carried to 38 weeks of gestation, and a phenotypically normal male baby was delivered without any abnormalities of the male external genitalia. The cord blood had a karyotypes of 46,X,i(Y) (q10)[8]/45,X[3]/46,XY [29], and placenta had a karyotypes of 45,X [25]/46,X,i(Y) (q10)[7]/46,XY [8]. When follow-up at age two months, the neonate was normal in development. The peripheral blood had a karyotypes of 46,X,i(Y) (q10)[8]/45,X[5]/46,XY [27]. Interphase fluorescence in situ hybridization (FISH) analysis on 101 buccal mucosal cells showed normal X and Y signals in 101/101 cells. Conclusion: Fetuses with 45,X/46, XY at amniocentesis can be associated with mosaicism for 46,X,i(Y) (q10) in the blood lymphocytes, cytogenetic discrepancy in various tissues and a favorable outcome.